Do review valence and review volume impact consumers' purchase decisions as assumed?. Issue 2 (6th June 2016) - Yang, Jing; Sarathy, Rathindra; Walsh, Stephen M.
Abstract : Purpose: To explore the psychological mechanism through which consumer reviews affect people's purchasing decisions and behavior, this study aims to examine the impact of statistical evidence embedded in product reviews on consumers' perceptions and purchasing intentions. Design/methodology/approach: The effects review valence and review volume are tested using a 3 (valence: positive vs neutral vs negative) × 2 (volume: high vs low) quasi-experimental design and online questionnaires. Findings: The study finds that review valence has a stronger impact on consumers' perceptions than review volume does. Negative reviews induce higher risk perception and a less favorable attitude toward purchases compared to positive reviews. In addition, although both attitude toward purchase and subjective norm are good antecedents of purchase intention, the attitude statistically has a stronger impact than the subjective norm. Research limitations/implications: This study contributes to extant literature from three perspectives. The authors have reexamined the findings of econometric models and advanced their implications by explaining the related psychological changes in people's perceptions. Second, the authors have extended the application of the theory of reasoned action and found it to be a good fit in explaining consumers' behavior related to consumer reviews. And finally, the authors have provided a clear guideline on the magnitude of the effects of review valence and volume on consumers' perceptions. Originality/value: This study provides a good complement to econometric studies from both theoretical and practical perspectives. It bridges the gap between exploratory studies and behavioral studies in the field of consumer reviews.